International experience in the prevention of criminal offenses in correctional institutionsInternational experience in the prevention of criminal offenses in correctional institutions - Turysbek, R.B.; Zhumagulova , Sh.R.; Satayeva , A.B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The urgency of preventing criminal offenses in correctional institutions against the background of the growing prison population and an increase in the number of recidivism, especially among those convicted of serious and especially serious crimes, is becoming one of the key problems of the modern penitentiary system in Kazakhstan. The need to improve the penal enforcement system requires the analysis and application of successful international practices. The research is aimed at studying foreign methods of crime prevention in places of detention and assessing their applicability in the conditions of Kazakhstan. The work examines various approaches, including criminological, legal and socio-psychological, as well as analyzes the factors influencing the criminal situation, such as social, economic and psychological aspects. The methodological basis of the research combines the study of literature, comparative analysis of international crime prevention models and a qualitative analysis of real cases from foreign systems. As a result, effective strategies that have been successfully implemented in the countries of the European Union, North America and Asia are identified. Among them are programs for the re-socialization and vocational training of convicts, the humanization of conditions of detention, the use of modern security technologies, as well as strict control and discipline measures. The results of the study confirm the effectiveness of an integrated approach based on rehabilitation and social adaptation of convicts, which helps to reduce the rate of recidivism and improve the criminogenic situation.